2011
DOI: 10.1002/ajmg.a.34137
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion at 4q21.3 is associated with intellectual disability, dysmorphic facies, hypotonia, and short stature

Abstract: Chromosomal imbalances are a major cause of intellectual disability (ID) and multiple congenital anomalies. We have clinically and molecularly characterized two patients with chromosome translocations and ID. Using whole genome array CGH analysis, we identified a microdeletion involving 4q21.3, unrelated to the translocations in both patients. We confirmed the 4q21.3 microdeletions using fluorescence in situ hybridization and quantitative genomic PCR. The corresponding deletion boundaries in the patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…PRKG2 influences anthropometric and blood pressure-related traits [Sung et al, 2015; Wood et al, 2014] and also affects multiple phenotypes in mice, including skeletal and adipose tissues. Humans with 4q21 microdeletion syndrome—which includes PRKG2 and flanking genes—show similar skeletal symptoms, including facial bone and growth retardations, but also neuropsychological symptoms, including speech and mental retardation [Bonnet et al, 2010; Dukes-Rimsky et al, 2011]. …”
Section: Discussionmentioning
confidence: 99%
“…PRKG2 influences anthropometric and blood pressure-related traits [Sung et al, 2015; Wood et al, 2014] and also affects multiple phenotypes in mice, including skeletal and adipose tissues. Humans with 4q21 microdeletion syndrome—which includes PRKG2 and flanking genes—show similar skeletal symptoms, including facial bone and growth retardations, but also neuropsychological symptoms, including speech and mental retardation [Bonnet et al, 2010; Dukes-Rimsky et al, 2011]. …”
Section: Discussionmentioning
confidence: 99%
“…Microdeletion 4q21 syndrome involves a core phenotype of growth delay with preserved head circumference, neonatal hypotonia, severe developmental delay, small hands and feet, and distinctive facial features consisting of frontal bossing, hypertelorism, and short philtrum [Bonnet et al, ; Dukes‐Rimsky et al, ]. A 1.37 Mb critical region, containing five genes, was defined in a group of nine patients [Bonnet et al, ].…”
Section: To the Editormentioning
confidence: 99%
“…Certainly, growth potential is limited in patients with microdeletion 4q21 syndrome: their reported heights and weights are uniformly low with widely varying OFCs (Supplementary Table I), delayed bone age was reported in the patient of Harada et al [] and both of the patients who were described in adulthood reached final heights >5 SD below average [Dukes‐Rimsky et al, ; Tsang et al, ]. On the other hand, feeding problems have been reported in several of these patients [McDermott et al, ; Nowaczyk et al, ; Dukes‐Rimsky et al, ; Bhoj et al, ], and generalized hypotonia is near‐universally present. Our patient's course illustrates that poor weight gain in children with microdeletion 4q21 syndrome may still reflect treatable problems such as dysphagia and malnutrition, not necessarily primary growth restriction alone.…”
Section: To the Editormentioning
confidence: 99%
“…This is a non‐recurrent genomic disorder, presented with overlapping deletions of different size at 4q21 region. Currently, 48 cases (18 from literature [Bonnet et al, ; Dukes‐Rimsky et al, ; Tsang et al, ; Bhoj et al, ; Bartnik et al, ; Komlosi et al, ; Sakazume et al, ] and 30 cases from databases) with defined genomic coordinates have been reported and the majority of individuals with 4q21 deletion are characterized by neonatal hypotonia, intellectual disability, absent or delayed speech, marked progressive growth retardation, and variable degrees of brain malformation and facial dysmorphism.…”
Section: Introductionmentioning
confidence: 99%